Administration, Science, and the State: The 1869 Population Census in Austria-Hungary. (14th July 2016) - Göderle, Wolfgang
Abstract : The population of Austria -Hungary was counted five times between 1869 and 1910. This process of counting established a new relationship between the state and its citizens. The state procured vast knowledge about its citizens, and the latter became accustomed to contact on a regular basis with state authorities and administrative practices. By the end of the nineteenth century, both the state and its citizens knew more of each other than ever before. This article scrutinizes the administrative translation of reality into discourse and the effects this had on the two parties involved.